(untitled) (Journal of Engineering, 2010)
Presented in this paper is a new study of the damaging effect of the tank loads on flexible pavements. The equivalent load was developed on the basis of mechanistic - empirical approach. It was found that the damaging effect of the studied tank loads is 0.898 to 2.356 times the damaging effect of the standard 18 kips (80 kN) axle load. It was found that the damaging effect of tank braking forces is 2.375 times the damaging effect of tank weight only in terms of tensile stain (fatigue cracking). It was found that the damaging effect of tank turning maneuver is 1.216 times the damaging effect of tank weight only in terms of tensile stain (fatigue cracking). These loads have also severe damaging effects on the functional serviceability of the surface of asphalt layer.